Herities of the semi-arid landscape: The Residual Reliefs of Alexandria-RN, Brazil - Henriques, Diógenys da Silva (2020)
This article aims to discuss about the residual reliefs of the semi-arid northeast, focusing on a case study conducted in the municipality of Alexandria in the Upper West Potiguar, Rio Grande do Norte, through which it presents as inheritances of the remarkable geomorphological features of the semiarid landscape of the sertão of the western northeastern region. Regarding methodological procedures, the research is systematized in two stages: office - bibliographic and geocartographic survey - and field - visit and recognition of the study area. We thus consider the theoretical studies of Ab'Saber (2003), Bertrand (2004), Lima et. al. (2009), Maia and Nascimento (2015; 2018), Souza and Oliveira (2002), in addition to cartographic interpretations about the geological and geomorphological characteristics of the area based on CPRM (2005). In this work, we verified the presence of predominant residual reliefs, as well as extensive areas of flagstones, that give an exuberant landscape in the interior of the northeastern hinterland of Rio Grande do Norte, with a granitic morphology, resulting from the formative process of endogenous and exogenous processes, in response to the constitution of the landscape as an inheritance, especially the Inselbergs.